1992
DOI: 10.1007/bf01710674
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus infection in patients with acute hepatitis B

Abstract: The prevalence of antibodies to hepatitis C virus (anti-HCV) was studied using a second-generation ELISA test in 121 patients with self-limiting acute hepatitis B, including 63 intravenous drug addicts (IVDA). Within the first month after the onset of illness, 47.1% of the patients were anti-HCV positive, this figure reaching 52.1% six months later. The prevalence in the sixth month was significantly higher in the IVDA (93.6%) than in the non-IVDA (6.9%) (p < 0.00001). Among the IVDA, anti-HCV was more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Most of the reports on acute coinfection occur in the settings of intravenous drug use, accidental needle stick, and blood transfusion [1719]. Acute coinfection can result in clearance of one or both viruses as described below, or can result in fulminant hepatitis or chronic coinfection.…”
Section: Natural History Of Hbv/hcv Coinfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the reports on acute coinfection occur in the settings of intravenous drug use, accidental needle stick, and blood transfusion [1719]. Acute coinfection can result in clearance of one or both viruses as described below, or can result in fulminant hepatitis or chronic coinfection.…”
Section: Natural History Of Hbv/hcv Coinfectionmentioning
confidence: 99%
“…In the setting of acute coinfection, spontaneous clearance of either or both viruses has been documented in the literature [17, 2123]. Mimms et al [21] observed that patients with coinfection had lower alanine transaminase (ALT) levels, delayed HBsAg appearance, and decreased HBs antigenemia, suggesting HCV suppression of HBV.…”
Section: Natural History Of Hbv/hcv Coinfectionmentioning
confidence: 99%
“…A cute coinfection of hepatitis B virus (HBV) and hepatitis C virus (HCV) is rare but more prevalent in intravenous drug abusers (1). The few previous cases all describe acute HBV followed by acute HCV, leading to HBV clearance but chronic HCV (1)(2)(3)(4).…”
mentioning
confidence: 99%
“…Indeed, concurrent infection with both HBV and HCV is growingly recognized in patients with acute and chronic hepatitis [220][221][222][223] . It has been reported that 22% of patients with HBV infection are tested positive with HCV [224][225][226][227][228] .…”
Section: Discussionmentioning
confidence: 99%